Comparative analysis of vitamin D contents in patients with chronic viral hepatitis C and healthy. - L. L. Shostakovych-Koretskaya; M. A. Nikolaychuk; I. V. Budayeva; O. P. Shevchenko-Makarenko; K. Yu. Lytviy; S. V. Biletska (Medičnì Perspektivi, 2020)
From scientific literature it is known that vitamin D helps maintain the most important functions of the immune system, there is evidence of its role in inflammatory and metabolic diseases of the liver, including infection with hepatitis C. Aim – to study vitamin D status in patients with chronic viral hepatitis C compared to the healthy ones. We examined 100 patients with chronic viral hepatitis C (main group) and 30 patients without hepatitis C virus (control group). Level of 25 (OH) D in serum was studied by immunochemical method with electrochemiluminescent detection. To verify the diagnosis of vitamin D deficiency and insufficiency, a classification (M.F. Holick, 2011), adopted by the International Institute of Medicine and the Committee of Endocrinologists for clinical practice guidelines, was used. Vitamin D deficiency was found in 44% of people with chronic viral hepatitis C in the main group (mean hydroxycalciferol – 14.36±4.12 ng/ml. Vitamin D deficiency was found in 6,6% in the control group (mean 17,5±8,52 ng/ml). The average vitamin D deficiency in the main group was slightly lower than that in the control group. Factors that affect the metabolism of vitamin D in patients with chronic viral hepatitis C include a lack of vitamin D in blood serum.